(untitled) (Global Journal of Medical Research, 2016)
The purpose of this paper was to obtain an enhanced understanding on the main factors that Medicare beneficiaries take into consideration before selecting a plan. This objective was fulfilled by interviewing a total of 16 Medicare beneficiaries from two south Florida counties. The participants were divided equally, 8 participants from Miami-Dade County and another 8 from Broward County. The researcher evaluated the differences between the populations from Miami-Dade County and Broward County participants to determine if there were any similarities. The researcher utilized one research question in order to fulfill the objective of the paper. By comparing the responses from the participants from both counties, health care plans that serve both counties can gain understanding of the differences between the populations.